The first zoea, megalopa, and first crab stage of the hydrothermal vent crab Xenograpsus testudinatus (Decapoda: Brachyura: Grapsoidea) and the systematic implications for the varunidae - Jeng, M.-S. (2014)
Journal of Crustacean Biology